Physiological and proteomic analyses of Saccharum spp. grown under salt stress - Murad, Aline Melro (2014)
Sugarcane (Saccharum spp.) is the world most productive sugar producing crop, making an understanding of its stress physiology key to increasing both sugar and ethanol production. To understand the behavior and salt tolerance mechanisms of sugarcane, two cultivars commonly used in Brazilian agriculture, RB867515 and RB855536, were submitted to salt stress for 48 days. Physiological parameters including net photosynthesis, water potential, dry root and shoot mass and malondialdehyde (MDA) content of leaves were determined. Control plants of the two cultivars showed similar values for most traits apart from higher root dry mass in RB867515. Both cultivars behaved similarly during salt stress, except for MDA levels for which there was a delay in the response for cultivar RB867515. Analysis of leaf macro- and micronutrients concentrations was performed and the concentration of Mn2+ increased on day 48 for both cultivars. In parallel, to observe the effects of salt stress on protein levels in leaves of the RB867515 cultivar, two-dimensional gel electrophoresis followed by MS analysis was performed. Four proteins were differentially expressed between control and salt-treated plants. Fructose 1,6-bisphosphate aldolase was down-regulated, a germin-like protein and glyceraldehyde 3 phosphate dehydrogenase showed increased expression levels under salt stress, and heat-shock protein 70 was expressed only in salt-treated plants. These proteins are involved in energy metabolism and defense-related responses and we suggest that they may be involved in protection mechanisms against salt stress in sugarcane.